Emerging Developments on Nanocellulose as Liquid Crystals: A Biomimetic Approach - Thiruganasambanthan, Theivasanthi; Ilyas, Rushdan Ahmad; Norrrahim, Mohd Nor Faiz; Kumar, Thiagamani Senthil Muthu; Siengchin, Suchart; Misenan, Muhammad Syukri Mohamad; Farid, Mohammed Abdillah Ahmad; Nurazzi, Norizan Mohd; Asyraf, Muhammad Rizal Muhammad; Zakaria, Sharifah Zarina Syed; Razman, Muhammad Rizal (MDPI, 2022)
Biomimetics is the field of obtaining ideas from nature that can be applied in science, engineering, and medicine. The usefulness of cellulose nanocrystals (CNC) and their excellent characteristics in biomimetic applications are exciting and promising areas of present and future research. CNCs are bio-based nanostructured material that can be isolated from several natural biomasses. The CNCs are one-dimensional with a high aspect ratio. They possess high crystalline order and high chirality when they are allowed to assemble in concentrated dispersions. Recent studies have demonstrated that CNCs possess remarkable optical and chemical properties that can be used to fabricate liquid crystals. Research is present in the early stage to develop CNC-based solvent-free liquid crystals that behave like both crystalline solids and liquids and exhibit the phenomenon of birefringence in anisotropic media. All these characteristics are beneficial for several biomimetic applications. Moreover, the films of CNC show the property of iridescent colors, making it suitable for photonic applications in various devices, such as electro-optical devices and flat panel displays.
Keywords: nanocellulose; cellulose nanocrystals; liquid crystals; biomimetic; CELLULOSE NANOCRYSTAL FILMS; SUPERHEATED STEAM; COLOR; SUSPENSIONS; PRETREATMENT; IRIDESCENCE; COMPOSITES; RHEOLOGY; AEROGELS; SCIENCE; Polymer Science